Penggunaan Aplikasi Triase Emergency Severity Index (ESI) - Widyawati, Wiwit; Kurniawati, Ninuk Dian; Wahyudi, Andri Setya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the use of the Emergency Severity Index (ESI) triage application in the Emergency Room (ER). The method used is a systemic review. The results of the study show that the use of this application is considered very effective in determining the accuracy of determining priorities due to the use of technology so that errors can be minimized compared to using the human mind. Conclusion from this study is that the use of the ESI application needs to be held in the ER to determine patient priorities appropriately. Keyword : Triage, ESI, Application